(untitled) (Agroindustrial Science, 2024)
Two studies were carried out with the aim of determining the digestible energy and the digestibility coefficient of the dry matter and protein of the rice polish; and assess the effect of five levels of rice polish (Oryza sativa) to replace wheat bran in diets for growing guinea pigs (Cavia porcellus) on productive parameters. In Study I, they were used 12 types I male guinea pigs with an average live weight of 875 g, the digestibility coefficients and digestible energy of rice polish were determined by the indirect method, with the total collection technique. The digestibility coefficient of dry matter was 80.33%, protein 75.51%, energy 78.06% and the digestible energy of rice polish was 3.77 Mcal/kg DM. In Study II, 80 type I improved male guinea pigs were used, of 14+2 days of age and average weight of 441 g, to evaluate the effect of five levels of rice polish: 0%, 4.5%, 7.5%, 15% and 30% in replacement of wheat bran, in 49-day growth diets. As a result, it was observed that there is no significant difference for weight gain, feed intake, feed conversion and carcass yield by replacing wheat bran with rice polish. The inclusion of rice polish at levels greater than 7.5 % affects the productive response in guinea pigs.